Hindari Pinjaman Online, Perkuat Kemandirian Keuangan Keluarga Bagi Jemat GKP Jakarta-Banten - Juaniva Sidharta; Carla Sucita; Elva Rohani Alya (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The community service activity with the theme “Avoid Online Loans, Strengthen Family Financial Independence” aims to provide understanding and solutions related to family financial problems faced by the congregation of the Pasundan Christian Church Jakarta-Banten Klasis. In recent years, the rapidly growing phenomenon of online loans has had a negative impact on society, especially in terms of family financial management. Many individuals are trapped in a cycle of debt that burdens the family economy. Through this activity, we conveyed information about the risks and impacts of online loans, as well as the importance of wise and healthy family financial management. In addition, participants were also given practical training on financial planning, savings strategies, and alternative financial solutions that are safer and more effective. It is hoped that with this activity, congregations can increase awareness about the importance of healthy finances and avoid the trap of online loans, so that families can be more financially independent and live in prosperity. The KPEJ GKP program of the Jakarta and Banten clasis considers it important to bring back a positive step that can educate the congregation about the risks of online loans and how to overcome them, namely by strengthening family financial independence for GKP congregations.